Belalang Kembar Siam Berkepala Dua sebagai Inspirasi Desain Busana Kostum untuk Perempuan - Dewi Isma Aryani; Cecilia Agata Purnama (JURNAL RUPA, 2023)
The extremely rare occurrence of conjoined twins in grasshoppers served as the inspiration for the POLYCHYPERA collection. Photographer Juan Camarillo from South America saw this two-headed grasshopper and utilized it as a photo subject for the image titled "Two Headed Grasshopper." By exhibiting one head's condition on the front-back and top-down sides of each outfit, the grasshopper's singularity serves as a source of inspiration for the design of costume apparel. The POLYCHYPERA costume collection is created with the contrast impact in mind. Finding a distinctive costume design development concept using an anthropomorphic approach is how the study challenge is stated. This study aims to develop a concept and product design for dramatic-styled costume garments. By experimentation and reading, the research method employs the project-based learning approach. The findings of this study are anticipated to serve as a guide for comparable fashion designs that can develop the innovative creativity of fashion industry players.